Tranilast Blunts the Hypertrophic and Fibrotic Response to Increased Afterload Independent of Cardiomyocyte Transient Receptor Potential Vanilloid 2 Channels. Issue 1 (July 2018) - Koch, Sheryl E.; Nieman, Michelle L.; Robbins, Nathan; Slone, Samuel; Worley, Mariah; Green, Lisa C.; Chen, Yamei; Barlow, Alexandria; Tranter, Michael; Wang, HongSheng; Lorenz, John N.; Rubinstein, Jack
Abstract : Abstract: Tranilast is clinically indicated for the treatment of allergic disorders and is also a nonselective blocker of the transient receptor potential vanilloid 2 (TRPV2) channel. Previous studies have found that it has protective effects in various animal models of cardiac disease. Our laboratory has found that genetic deletion of TRPV2 results in a blunted hypertrophic response to increased afterload; thus, this study tested the hypothesis that tranilast through cardiomyocyte TRPV2 blockade can inhibit the hypertrophic response to pressure overload in vivo through transverse aortic constriction and ex vivo through isolated myocyte studies. The in vivo studies demonstrated that tranilast blunted the fibrotic response to increased afterload and, to a lesser extent, the hypertrophic response. After 4 weeks, this blunting was associated with improved cardiac function, although at 8 weeks, the cardiac function deteriorated similarly to the control group. Finally, the in vitro studies demonstrated that tranilast was not inhibiting these responses at the cardiomyocyte level. In conclusion, we demonstrated that tranilast blunting of the fibrotic and hypertrophic response occurs independently of cardiac TRPV2 channels and may be cardioprotective in the short term but not after prolonged administration.